2019
DOI: 10.3390/metabo9050095
|View full text |Cite
|
Sign up to set email alerts
|

Ovothiol A is the Main Antioxidant in Fish Lens

Abstract: Tissue protection from oxidative stress by antioxidants is of vital importance for cellular metabolism. The lens mostly consists of fiber cells lacking nuclei and organelles, having minimal metabolic activity; therefore, the defense of the lens tissue from the oxidative stress strongly relies on metabolites. Protein-free extracts from lenses and gills of freshwater fish, Sander lucioperca and Rutilus rutilus lacustris, were subjected to analysis using high-field 1H NMR spectroscopy and HPLC with optical and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…For example, ovothiols have been reported to induce egg release in marine polychaetes during sexual reproduction [53]. Interestingly, ovothiols might play important roles also in animals that, although lacking the biosynthetic pathway, might acquire this bioactive compound from external sources [49,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…For example, ovothiols have been reported to induce egg release in marine polychaetes during sexual reproduction [53]. Interestingly, ovothiols might play important roles also in animals that, although lacking the biosynthetic pathway, might acquire this bioactive compound from external sources [49,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The extracts for NMR measurements were re-dissolved in 600 μL of D 2 O containing 6 × 10 −6 M sodium 4,4-dimethyl-4-silapentane-1-sulfonic acid (DSS) as an internal standard and 20 mM deuterated phosphate buffer to maintain pH 7.2. The 1 H-NMR measurements were carried out in the Center of Collective Use «Mass spectrometric investigations» SB RAS on a NMR spectrometer AVANCE III HD 700 MHz (Bruker BioSpin, Germany) equipped with a 16.44 T Ascend cryomagnet as described in 43 . The proton NMR spectra for each sample were obtained with 64 accumulations.…”
Section: Animals R Amurensis Individuals Were Collected In Septembementioning
confidence: 99%
“…In this work, LC-MS measurements were performed only for the confirmation of data obtained by the NMR method. The LC separation was performed on a UltiMate 3000RS chromatograph (Dionex, Germany) using a hydrophilic interaction liquid chromatography (HILIC) method on a TSKgel Amide-80 h (Tosoh Bioscience, Germany) column (4.6 × 250 mm, 5 μm) as described earlier 43 . The MS detection in both positive and negative modes was performed with the use of an ESI-q-TOF high-resolution hybrid mass spectrometer maXis 4G (Bruker Daltonics, Germany) connected to the chromatograph.…”
Section: Lc-ms Measurementsmentioning
confidence: 99%
“…The major antioxidant of the fish lens is OSH 12 . It has been shown that the level of OSH in S. lucioperca lens vary from 3 µmol/g at autumn to 1.5 µmol/g at winter 15 , which is in a good agreement with our present data ( Table 1).…”
Section: Discussionmentioning
confidence: 99%